Dietary Intake of Nutrients and Lifestyle Affect the Risk of Mild Cognitive Impairment in the Chinese Elderly Population: A Cross-Sectional Study - Lu, Yanhui; An, Yu; Guo, Jin; Zhang, Xiaona; Wang, Hui; Rong, Hongguo; Xiao, Rong (Frontiers in Behavioral Neuroscience, 2016)
Mild cognitive impairment (MCI) is a pre-clinical stage of Alzheimer’s disease afflicting a large number of the elderly throughout the world. However, modifiable risk factors for the onset and progression of MCI remain unclear. A cross-sectional study was performed to explore whether and how daily dietary nutrients intake and lifestyle impacted the risk of MCI in the Chinese elderly. We examined 2,892 elderly subjects, including 768 MCI patients and 2,124 subjects with normal cognition in three different Provinces of China. Dietary intake of nutrients were collected by using a 33-item food frequency questionnaire (FFQ) and calculated based on the Chinese Food Composition database. The MCI patients were first screened by Montreal Cognitive Assessment (MoCA) and then diagnosed by medical neurologists. Multivariate logistic regression and exploratory factor analyses were applied to identify and rank the risk factors. Three dietary nutrient intake combination patterns were identified as the major protective factors of MCI, with eigenvalues of 14.11, 2.26 and 1.51 and adjusted odds ratios (OR) of 0.77, 0.81, and 0.83 (P < 0.05), respectively. The most protective combination was featured with 8 vitamins and 6 minerals, and OR for the third and fourth quartiles of these nutrients intake ranged from 0.48 to 0.74 (P < 0.05). Carotenoids, vitamin C, and vitamin B6 exhibited the highest protective factor loadings of 0.97, 0.95, and 0.92 (P < 0.05), respectively. Education, computer use, reading, and drinking represented the most protective lifestyle factors (OR = 0.25 to 0.85, P < 0.05), whereas smoking and peripheral vascular diseases were associated with higher (OR = 1.40 and 1.76, P < 0.05) risk of MCI. Adequate dietary intake of monounsaturated fatty acids and cholesterol were significantly associated with decreased risk of MCI. In conclusion, adequate or enhanced intake of micronutrients seemed to lower the risk of MCI in the Chinese elderly. In addition, improving education and lifestyle such as reading, computer use and moderate drinking might also help to decrease the risk of MCI.